PENGUATAN LITERASI DIGITAL KEAGAMAAN DALAM MENUMBUHKAN SIKAP MODERASI BERAGAMA PADA ANGGOTA IPNU-IPPNU DESA NGAMBEG - Novitasari, Lenny; Futaqi, Sauqi; Saefrudin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Digital transformation has encouraged younger generations to access religious information through various online platforms; however, the limited ability to filter content may foster intolerant attitudes and expose users to radical narratives. This study aims to describe the understanding and practice of religious digital literacy, analyze efforts to strengthen it, and identify forms of religious moderation among members of IPNU-IPPNU in Ngambeg Village, Pucuk District, Lamongan Regency. A qualitative descriptive method was employed, utilizing triangulation techniques consisting of participatory observation, semi-structured interviews, and documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña, encompassing condensation, data presentation, and conclusion drawing. Findings reveal that members utilize YouTube, Instagram, WhatsApp, and TikTok as sources of Islamic knowledge while upholding the principle of tabayyun in verifying information. Strengthening efforts were carried out through cadre development programs, Islamic studies, and digital literacy training facilitated continuously by organizational leaders and supervisors. As a result, members demonstrated concrete religious moderation, including tolerance, openness to diverse opinions, rejection of hoaxes and radicalism, deliberative culture, and a balance between spiritual and social dimensions. It is concluded that strengthening religious digital literacy and religious moderation are two mutually reinforcing elements in nurturing a tolerant and adaptive younger generation.